Pruritic Urticarial Papules and Plaque of Pregnancy (Puppp) and Homoeopathy: A Case Study (Advancements in Homeopathic Research, 2022)
Polymorphic Eruption of Pregnancy (PEP) is a specific dermatosis of pregnancy. This is also known as Pruritic Urticarial Papules and Plaque of Pregnancy (PUPPP). PEP is a benign, self-limiting skin disorder which disappears one month following delivery.(6) An increased prevalence is noted mainly in primigravida.The remission can be seen at time of delivery.(1)During pregnancy, there are many hormonal changes and thus there can be many dermatological complications. In homoeopathy, medications are given on the basis of individualization. Thus, these dermatological changes can be well managed by homoeopathy.
Keywords: Pruritic Urticarial Papules and Plaque of Pregnancy; Gestational Dermatosis; Homoeopathy; Case report; Apis mellifica; Sulphur